The Correlation between Insomnia with Blood Pressure in the Elderly in Banjar Wangaya Kajathe Work Area of Public Health Center III North Denpasar - Yuni Antari; Sang Ayu Ketut Candrawati; Putu Gede Subhaktiyasa (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Elderly is a term for an individual who has entered the period of late adolescence or old age. The number of elderly in the province of Bali in 2018 reached 572.518 inhabitants. Elderly degeneration in terms of both aspects of the psychological and physiological aspects. One form of setbacks is a sleep disorder (insomnia). Insomnia is a disorder of the quantity and quality of sleep that inhibit its function. The elderly who suffer from insomnia to be an increase in sympathetic activity will increase blood pressure and decreased parasympathetic activity lowers blood pressure, in which blood pressure is influenced by the autonomous system that is sympathetic and parasympathetic. This study aims to determine the correlation betweeninsomnia with blood pressure in the elderly in Banjar Wangaya Kaja the work area of Public Health Center III North Denpasar. This research is an analytic correlational research aimed to see whether or not the correlation insomnia with blood pressure exist in the elderly by using cross sectional approach. The sample consisted of 88 respondents to the sampling technique used purposive sampling. Collecting data using questionnaires insomnia and blood pressure measurements using a mercury sphygmomanometer. Most elderly people experience severe insomnia that 68 (77.3%), and as many as 58 people (65.9%) of elderly hypertensive level 1. Based on the results-Spearman rank correlation test in getting the results p (value) = 0,000 <0 , 05 then Ho is rejected and Ha accepted which means there is a significant correlation between insomnia with blood pressure in the elderly in Banjar Kaja Wangaya. The results showed a correlation coefficient of r = 0,702,, it means the correlation is in a strong level, the positive direction of correlation means the higher the insomnia in the elderly, the higher blood pressure will be